Synthesis of Blue Pigment from Kaolin: Synthesis of Blue Pigment - Rahman, Amin Ur; Khan, Faridullah; Riaz, Muhammad; Latif, Atif (Biological Sciences - PJSIR, 2009)
Kaolin of Swat NWFP, Pakistan was analyzed and its suitability was tested for utilizing the raw material for the synthesis of blue pigment. It was successfully utilized for the preparation of ultramarine blue pigment by subsequent reductive and oxidative heating with other ingredients. The pigment was characterized by UV-Vis, IR spectrophotometry and XRD.